PENGENALAN HURUF BERBASIS ECOBRIK DI SEKOLAH DASAR - Wauyai, Salbia; Yulianto, Ahmad; Asrul, Asrul (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to produce ecobrick-based letter recognition media for grade 1 in elementary school that is valid, practical and effective. This type of research is Research and Development (R&D) research. The development of this learning media was designed using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The test subjects used in this research were 14 grade 1 students at SD Negeri 8 Sorong City. The results of this research show that: 1) Based on validity test data from material expert validators, language experts and design experts, the ecobrick-based letter recognition media for grade 1 elementary school shows a valid category so it is suitable for use. 2) Based on practicality test data from the results of the student response questionnaire, this ecobrick-based letter recognition media obtained an average score of 79 so it can be categorized as practical. 3) Based on the effectiveness test data from the results between the pre-test and post-test using the n-gain test, this ecobrick-based letter recognition media is very effective to use, this can be seen from the average score obtained being 0.74 so it can be categorized as high. Based on the results of this research, it can be concluded that ecobrick-based letter recognition media is valid and suitable for use in the learning process.